2008
DOI: 10.1057/emr.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Psychological antecedents to socially responsible behavior

Abstract: To date, the discussion regarding corporate social responsibility (CSR) has primarily addressed organizational rationale and activities. Little has been said about the individual characteristics and behaviors that promote the development of CSR within organizations. In this paper, we propose and test a model to explain individual differences in the propensity to engage in socially responsible behavior (SRB). By linking values, affect and reasoning to managers' propensity to ‘do good’ and ‘do no harm,’ we provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 125 publications
(102 reference statements)
0
92
0
3
Order By: Relevance
“…Scant research has examined employees' discretionary behaviors that target the social level or, in other words, that intend to enhance the well-being of their organization's stakeholders, including the natural environment (Crilly et al 2008;Daily et al 2009;Vlachos et al 2014). Accordingly, (Roeck & Farooq, 2017) examine societal outcome by employees' engagement in green behaviors, including employees' actions to perform work in an environmentally friendly way (e.g., recycling, rational use of resources, participation in environ-mental initiatives, setting of more sustainable policies), and societal behaviors, http://dx.doi.org/10.15405/epsbs.2018.05.63 Corresponding Author: Abdul Sami Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 774 including employees' actions that support overall community well-being even outside the work context.…”
Section: Societal Outcomementioning
confidence: 99%
“…Scant research has examined employees' discretionary behaviors that target the social level or, in other words, that intend to enhance the well-being of their organization's stakeholders, including the natural environment (Crilly et al 2008;Daily et al 2009;Vlachos et al 2014). Accordingly, (Roeck & Farooq, 2017) examine societal outcome by employees' engagement in green behaviors, including employees' actions to perform work in an environmentally friendly way (e.g., recycling, rational use of resources, participation in environ-mental initiatives, setting of more sustainable policies), and societal behaviors, http://dx.doi.org/10.15405/epsbs.2018.05.63 Corresponding Author: Abdul Sami Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 774 including employees' actions that support overall community well-being even outside the work context.…”
Section: Societal Outcomementioning
confidence: 99%
“…Researchers have analyzed the influence of personal values in shaping social and economic behaviors. For instance, Crilly et al (2008) found association between personal values and moral reasoning that leads to pro-social behavior among individuals. Similarly, Lonnqvist, Verkasalo, Wichardt, and Walkowitz (2013) examined the association between personal values and pro-social behaviors.…”
Section: Personal Values and Socially Responsible Behaviormentioning
confidence: 99%
“…Benevolence refers to set of values "preserving and enhancing the welfare of those with whom one is in frequent personal contact" (Schwartz, 1992). Crilly et al, (2008); Egri and Herman (2000); and Whitener, Susan, Brodt, Audrey, and Jon (1998) noted that people who have concern for others (self-transcendence) have more pro-social behavior. Sagiv, Sverdlik, and Schwarz, (2011) argued that self-transcendence values promotes pro-social behavior.…”
Section: Personal Values and Socially Responsible Behaviormentioning
confidence: 99%
See 2 more Smart Citations